Paddy grading using thermal imaging technology - Bejo, Siti Khairunniza; Azman, Norsolehah; Jamil, Norazlida (2015)
Rice production depends on good quality of paddy. In this research, the capability of thermal imaging to determine the quality of paddy based on the parameters used in a Deduction Schedule namely moisture content, immature condition and foreign material is presented. Average value of pixels in the thermal image will be used as the feature for determination. Heating and cooling treatment has been applied to the samples. Meanwhile, results of the experiment have shown that thermal image can be used to determine moisture content of paddy. There is a high significant relationship with R2 = -0.948 and successfully determine value of moisture content with 92% accuracy. Results of maturity stage determination had shown that there’s significant linear relationship between average intensity of thermal image and the paddy maturity stage with R2 = 0.896. The more matured the paddy, the higher the value of its mean pixel. This method also successfully predicts maturity of paddy with 90% accuracy. Finally, results of the chaff detection had shown that the mean pixel of seed thermal image is higher compared to chaff. Mean pixel value at 25s gave significant difference to separate between paddy and chaff. The technique can detect 40% of chaff inside paddy images with 100% accuracy.